MODEL BRAINSTORMING UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA - Fatma Khaulani; Taufina Taufina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to improve the quality of PKn grade V learning at SDN 009 Pulau through the application of the Brainstorming model. This research is a class action research consisting of III cycles. The subject of research is the fifth grade students of SDN 009 Pulau Bangkinang District. The results showed an increase in each variable in each cycle. The increase of Civics learning outcomes from an average base score of 62.50 to 69.06 in the first cycle, in the second cycle increased to 75.93 and in the third cycle increased to 80.94. Improved learning outcomes that occur base score to UH I is 10.49%, on UH II scores to 21.49%, and on UH III to 29.50%. The brainstorming model has been proven to be able to improve the quality of learning of PKn grade V SDN 009 Pulau.Keywords: brainstorming, civics, learning outcomes